Description of Emotion Through Dialog in Webtoon ‘It's Mine’ - Ochy Caramoy; Otong Djuharie (INDO PUBLISHING, 2025)
This study aims to analyze how Emotions are displayed through language choices and speech styles in the Webtoon 'It's Mine'. As a visual narrative media that is widely favored by young people, 'It's Mine' features characters with complex psychological dynamics that are reflected not only in the illustrations, but also in the use of distinctive and expressive language. Using a critical discourse analysis approach as well as a basic psycholinguistic framework, this study will identify forms of language expression related to the characters' emotional states, such as sentence structure, diction, tone, and conversational context in dialog. The data is taken from a number of core episodes that feature conversations containing emotions that refer to mental character issues. The expected result is an understanding of the role of language as a medium for depicting psychological conditions in modern digital narratives, as well as how readers interpret characters' emotional communication indirectly through language choices. This research is expected to contribute to the study of language in popular media and the representation of character psychology through digital texts.